MODEL FUZZY TAHANI UNTUK PEMODELAN SISTEM PENDUKUNG KEPUTUSAN (SPK) - Lia Amalia; Zainuddin Bey Fananie; Ditdit N. Utama (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2010)
Decision making paradigm has changed. Many managers in many companies have used DecisionSupport System (DSS) to optimize their decision making. Modified DSS by using web infrastructure has helpedmanagers make decision more effective and accurate. Web based DSS is not used by managers only, butpersonal aim too. In this paper, authors tried to explain the TahaniFuzzyModelmethodology that used indeveloping model of DSS, in handphone purchasing case. The customer purchasing behavior / style andhandphone features combination is used as data or information to analyze DSS model. On the other hand, DSSdevelopment used structured system developing methodology.Keywords: Decision Support System, Handphone, TahaniFuzzy Model